2020
DOI: 10.3390/molecules25184058
|View full text |Cite
|
Sign up to set email alerts
|

Retrofractamide C Derived from Piper longum Alleviates Xylene-Induced Mouse Ear Edema and Inhibits Phosphorylation of ERK and NF-κB in LPS-Induced J774A.1

Abstract: Many studies have reported the biological activities of retrofractamide C (RAC). However, few studies have investigated the anti-inflammatory effect of RAC. In the present study, we investigated the anti-inflammatory effect of RAC using lipopolysaccharide (LPS)-induced J774A.1 cells and a xylene-induced mouse ear edema model. Treatment with RAC decreased LPS-induced nitric oxide (NO) and prostaglandin E2 (PGE2) secretion and inducible NO synthase (iNOS) and cyclooxygenase 2 (COX2) protein expression. It also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…edema. 36 In our study, it was shown that the essential oil of E. camaldulensis at 400 mg/kg dose can markedly inhibit (67.75%) the formation of xylene-induced ear edema while the standard diclofenac Na was found to show the highest inhibition 83.67%.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…edema. 36 In our study, it was shown that the essential oil of E. camaldulensis at 400 mg/kg dose can markedly inhibit (67.75%) the formation of xylene-induced ear edema while the standard diclofenac Na was found to show the highest inhibition 83.67%.…”
Section: Discussionmentioning
confidence: 64%
“…This method has been frequently used to initiate acute inflammatory response which leads to serious edematous changes and vasodilation of skin when topically applied to the surfaces of the ears of mice. 36,37 Xylene initiates the release of inflammatory mediators, which promotes vasodilation and increasing vascular permeability, and causes ear Values are presented as mean ± SEM (n = 6). One-way ANOVA followed by Dunnett's multiple comparisons was performed to analyze this dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin‐1β (IL‐1β) and interleukin‐6 (IL‐6) expression were downregulated and phosphorylation of extracellular signal‐regulated kinase (ERK) and nuclear factor kappa light chain enhancer of activated B cells (NF‐κB) were inhibited. RAC treatment also alleviated oedema formation and inflammatory cell infiltration in the xylene‐induced mouse ear oedema model (Lim et al, 2020).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…PGE-2 is one of the major inflammatory mediators in the tissue. It is known that following the xylene application, the level of PGE-2 increases, causing vasodilation and swelling of the ear tissue in combination with the effects of various mediators [68,69]. PGE-2 is also involved in numerous skinrelated conditions (including cancer, aging, UV-light exposure, etc.)…”
Section: In Vivo Studiesmentioning
confidence: 99%